Herd structure in the bovine Calvana breed - A. Giorgetti (Italian Journal of Animal Science, 2010)
Farm structure is one of the principle components that influence profit, sustainability and survival of a herd, especially in endangered breeds. The sustainability of these herds is based on the capability to take advantage of specific niches of the market, of specific label or organic certification or “designation of geographical indications or origin for agricultural products”.